Subjective Social Status and Cardiovascular Reactivity: An Experimental Examination - Pieritz, Karoline; Süssenbach, Philipp; Rief, Winfried; Euteneuer, Frank (Frontiers in Psychology, 2016)
The present experiment examined the causal influence of subjective social status (SSS) on variables related to cardiovascular health (i.e., blood pressure, heart rate variability [HRV]). Participants were randomly assigned to one of two conditions involving a social comparison that either induced a temporary shift toward high SSS or toward low SSS. Cardiovascular variables were measured before (baseline), throughout, and after the manipulation (recovery). Participants in the low SSS condition had a significantly lower HRV during experimental manipulation than at baseline. They also showed a significantly stronger HRV reactivity compared to participants in the high SSS condition. Our results suggest that already temporary shifts of one’s SSS have measureable effects on cardiovascular variables. They support the notion that social status plays a causal role in the development of cardiovascular disease.